Analisis Proses Pembelajaran Daring Terhadap Guru dan Siswa Pada Masa Pandemi Covid 19 - Aryadhana Aryadhana; Asmin Asmin (Journal Mathematics Education Sigma [JMES], 2022)
Abstract. This study aims (1) to determine the learning system in the network (online) that can be viewed from the aspect of learning planning. (2) To find out the results of the online learning process for teachers and students. (3) To find out the impact of the advantages and disadvantages of applications (Google Meet, Classroom and Zoom) on the online learning process. (4) To determine the preparation of teachers and students for the online learning process with inadequate facilities. This research is a qualitative research with a descriptive approach. The subjects in this study were mathematics teachers and students in class VII-2 of SMP Negeri 1 Percut Sei Tuan T.A 2021/2022. The instruments in this study were questionnaires and interviews. Questionnaire and interview guide are valid. From the results of the study, it was found that because the teacher had followed the procedures in the design of the learning process to follow the online learning process. Therefore, in the online learning process that uses applications (WhatssApp, Gmeet and Google Classroom) the teacher will find it easier to provide material, direction and motivation for students in detail and the teacher is more active in giving learning videos to students in the material being taught. The results of the online learning process for teachers and students in the learning process are very satisfying. This is because the effectiveness of the online learning process carried out by teachers and students is very efficient and some students who take part in the offline learning process are also effective. Abstrak. Penelitian ini bertujuan (1) untuk mengetahui sistem pembelajaran dalam jaringan (daring) yang dapat dilihat dari aspek perencanaan pembelajaran. (2) Untuk mengetahui hasil dari proses pembelajaran daring bagi guru dan siswa. (3) Untuk mengetahui dampak kelebihan dan kekurangan aplikasi (Google Meet, Classroom dan Zoom) terhadap proses pembelajaran daring. (4) Menentukan persiapan guru dan siswa untuk proses pembelajaran daring dengan fasilitas yang kurang memadai. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif. Mata pelajaran dalam penelitian ini adalah guru matematika dan siswa kelas VII-2 SMP Negeri 1 Percut Sei Tuan T.A 2021/2022. Instrumen dalam penelitian ini adalah kuesioner dan wawancara. Kuesioner dan panduan wawancara valid. Dari hasil penelitian tersebut ditemukan bahwa karena guru telah mengikuti prosedur dalam perancangan proses pembelajaran untuk mengikuti proses pembelajaran daring. Oleh karena itu, dalam proses pembelajaran daring yang menggunakan aplikasi (WhatssApp, Gmeet dan Google Classroom) guru akan lebih mudah memberikan materi, arahan dan motivasi bagi siswa secara detail dan guru lebih aktif dalam memberikan video pembelajaran kepada siswa dalam materi yang diajarkan. Hasil dari proses pembelajaran daring bagi guru dan siswa dalam proses pembelajaran sangat memuaskan. Hal ini dikarenakan efektivitas proses pembelajaran daring yang dilakukan oleh guru dan siswa sangat efisien dan beberapa siswa yang mengikuti proses pembelajaran luring juga efektif.